HUBUNGAN KARAKTERISTIK SOSIAL EKONOMI DENGAN TINGKAT ADOPSI PETANI PADI ORGANIK DI KECAMATAN SEPUTIH RAMAN KABUPATEN LAMPUNG TENGAH - Ainul Mardliyah (Jurnal WACANA PERTANIAN, 2018)
The objective of this research to determine corelation between socio economic characteristic and organic rice farmers adaption in the District of Seputih Raman Central Lampung Regency. The research method used is survey method, which was conducted in Rejo Asri Village Seputih Raman District, Central Lampung Regency. The study was conducted in November-December 2017. Sampling in this study was conducted by census with the number of samples was 20 farmers. The analysis used is Rank Spearman analysis. The result of this research can be concluded that there is correlation between socio economic characteristic (age, farming experience, extension) with adoption rate of organic rice farmer. While for the variable of education and land area is not related to the adoption rate of organic rice farmers in the District of Seputih Raman of Central Lampung Regency. Keyword: Socio Economic Characteristics, Adoption Rate, Organic Rice.